Effect of land use on plant nutrient availability and soil carbon sequestration of Mokonisa Machi Watershade, Dugda Dawa District of Southern Ethiopia - Geneti, Tadele; Tamiru, Haile; Singh, Vijay; Godana, Nuguse (Indian Journal of Plant Protection, 2023)
Different land use practices have a varied impact on soil degradation as reflected by physical and chemical properties as well as soil carbon sequestration capacity. Meager studies have examined the effects of land use on plant nutrient availability and soil carbon sequestration in Ethiopia. Therefore, the present study was conducted to investigate the effects of land use on plant nutrient availability and soil carbon sequestration in Mokonisa Machi Watershade (10 km away from Bule Hora University), Dugda Dawa District of Ethiopia. Our study specifically found the differences between three different land use types on soil texture, soil pH, cation exchange capacity, organic carbon, total nitrogen, available phosphorus, exchangeable potassium and the implication of the farming practices on soil carbon sequestration. Soil samples were collected from 0-15 and 15-30 cm layer of forest land, cultivated land and grazing land. The soil texture belonged to mainly clay and heavy clay textural class. Along with soil depths, the bulk density showed an increasing trend from 1.12 to 1.27g/cm in all sampling sites. While decreasing trends were recorded in soil organic carbon, organic matter, cation exchange capacity, % total nitrogen, available phosphorous and exchangeable potassium. Marginal increase in pH was recorded with increase in soil depths of all land use systems. The average total soil organic carbon sequestration in forest, grazing and farm land was recorded was 95.2, 88.45 and 65.5 t/ha, respectively for surface soil, while 93.3, 73.75 and 62.5 t/ha, respectively for sub-surface soil. Thus, plant nutrient and soil fertility improvement are the most important management interventions to increase the soil productivity and production capacity of agricultural crops. Therefore, stakeholders should focus on management activities that improve the plant nutrient and bulk density to boost carbon sequestration capacity of the soil.